Konformitas ditinjau dari Jenis Kelamin pada Remaja - Rahmadillah, Suci; Alfita, Laili (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Conformity is a type of social influence that encourages individuals to adjust their attitudes and behaviors to align with prevailing social norms. This study aims to explore gender differences in conformity among adolescents. It is hypothesized that there are slight differences in the levels of conformity exhibited by males and females, influenced by the social situations in which conformity occurs and inherent gender differences. The study adopts a literature review approach to identify, evaluate, and interpret relevant research findings on this topic. This process involves evaluating and summarizing existing studies, incorporating insights from recent and earlier publications to provide a comprehensive overview. The findings indicate that females tend to exhibit higher levels of conformity compared to males. Females are more inclined to prioritize interpersonal relationships and maintain group harmony. In contrast, males are generally more concerned with displaying high status and are likely to demonstrate this status through independent actions in decision-making, thinking, and expressing opinions. These results illustrate the role of gender in shaping conformity, influenced by social norms and group dynamics.